PENGARUH LATIHAN PLYOMETRICS TERHADAP KEMAMPUAN LOMPAT JAUH GAYA JONGKOK SISWA SMA NEGERI 09 BOMBANA - Muhammad Fajri; Abdul Saman; Badaruddin (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the effect of plyometrics training (depth jump) on the long jump ability of the students of SMA Negeri 09 Bombana, Poleang Tengah District, Bombana Regency. The formulation of the problem in this research is, is there any effect of plyometrics training (depth jump) on the ability of the long jump squat style of SMA Negeri 09 Bombana students, Poleang Tengah District, Bombana Regency? The population in this study were students of SMA Negeri 09 Bombana totaling 260 students consisting of 136 boys and 124 girls, the sample in this study was obtained using a purposive sampling technique, namely the sample was selected with consideration of male gender and was taken using a lottery that the researchers wanted, namely 31 students. The instrument used to measure the long jump ability was using the long jump test which was carried out 3 times for each student while the treatment was plyometrics (depth jump). The data in this study were analyzed using descriptive statistical techniques and inferential tests through t-test and Anova test. with a significant level of 0.05 where the results obtained from hypothesis testing show that t count = 17.296 > t table at a significant level (0.05: 30) = 1.5. This research can be concluded that there is an effect of plyometrics training (depth jump) on the ability of the long jump squat style of SMA Negeri 09 Bombana, Poleang Tengah District, Bombana Regency.